2012
DOI: 10.1590/s0365-05962012000300007
|View full text |Cite
|
Sign up to set email alerts
|

The profile of the dermatoses in children with the HIV virus at the Fundação de Medicina Tropical do Amazonas

Abstract: BACKGROUND: The Acquired Immunodeficiency Syndrome (AIDS) constitutes a sub-epidemic in Brazil. Due to the increasing number of women infected by the virus, the vertical transmission increased substantially, and due to the lack of adequate prophylactic treatment, many children are infected and show manifestations of the disease in early ages. Multiple systems are affected by the HIV virus, and the skin is often the first organ to be involved. OBJECTIVES: The objective of this study is to analyze the clinic, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…One was caused by cotrimoxazole, another because of ceftriaxone, and the third was caused by efavirenz. 13 There was no significant difference in the percentage of manifestations between those who were on ART (59%) and those who were not (63%). In the study by Doni et al, there was no significant difference in the prevalence of skin disease between children receiving ART and those who were not.…”
Section: Percentage Of Skin Manifestations Within Cd4 Categorymentioning
confidence: 86%
See 1 more Smart Citation
“…One was caused by cotrimoxazole, another because of ceftriaxone, and the third was caused by efavirenz. 13 There was no significant difference in the percentage of manifestations between those who were on ART (59%) and those who were not (63%). In the study by Doni et al, there was no significant difference in the prevalence of skin disease between children receiving ART and those who were not.…”
Section: Percentage Of Skin Manifestations Within Cd4 Categorymentioning
confidence: 86%
“…In the study by Dias et al ., drug rash was seen in three patients. One was caused by cotrimoxazole, another because of ceftriaxone, and the third was caused by efavirenz . In a case report by Norris et al., a 10‐year‐old female was given a combination of antiretroviral drugs (lamivudine, nevirapine, and stavudine) as post‐exposure prophylaxis and developed TEN …”
Section: Discussionmentioning
confidence: 99%
“…In a study performed on hospital HIV inpatients and outpatients, a clinical evaluation of 796 cases revealed that 19.2% of them had eczema [27]. It was found to be the most frequent type of dermatitis among 70 children with HIV treated at the Tropical Medicine Foundation of Amazonas, detected in 22.9% [26]. These studies included a clinical evaluation of the patients; therefore, they may provide more reliable information on the true prevalence of eczema in children with HIV.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the prevalence of dermatoses in HIV-infected children indicate a high incidence of viral, fungal and bacterial infections of the skin, compared with HIV-negative children [1]. Dias et al (2012) determined the profile of dermatoses in children living with HIV at the Fundação de Medicina Tropical do Amazonas and concluded that children with HIV / AIDS have more non-infectious dermatoses than healthy children. According to the authors, atopic dermatitis was most often recorded (22.9%) [2].…”
Section: Introductionmentioning
confidence: 99%
“…Dias et al (2012) determined the profile of dermatoses in children living with HIV at the Fundação de Medicina Tropical do Amazonas and concluded that children with HIV / AIDS have more non-infectious dermatoses than healthy children. According to the authors, atopic dermatitis was most often recorded (22.9%) [2].…”
Section: Introductionmentioning
confidence: 99%